APRESIASI MASYARAKAT JORONG MAPUN KENAGARIAN SUNDATA KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN TERHADAPKESENIAN RUPANO DALAM TRADISI BAARAK-ARAK BALIMAU - Fitra Hayati; Marzam Marzam; Esy Maestro (SENDRATASIK UNP, 2018)
AbstractThis study aimed to reveal and explain the appreciation of Jorong and Nagari Community of Sundata, Lubuk Sikaping District, Pasaman Regency towards the existence of Rupano art. Data were obtained through direct observation, interview, literature study, and documentation. The data were analyzed based on phenomenon that happened to the existence of rupano art and society appreciation to the art by using Miles and Huberman model.The results show that the public appreciation on rupano art is lack, so even though this art is performed, people are not interested anymore to wacth it. The level of public appretiation of rupano art is ound very low. Society does not recognize and understand the details or specifics and aesthetis o the rupano art. Therefore people have not appreciated the art of rupano well. In addition, the community also has no sense of responsibility and sense of belonging to the arts. This because the general public has been bored o watching the rupano art for the reasons of rupano art is not impressing it has no development althogether.